Ilex namkadingensis: a new species of Aquifoliaceae from central Laos - Dang, V. S.; Souladeth, P.; Nguyen, Q. B.; Kongxaisavath, D.; Phengmala, K.; Sengthong, A.; Souvannakhoummane, K.; Vongthavone, T.; Yamamoto, T.; Tanaka, N.; Takahashi, K. T.; Tagane, S. (Rheedea, 2025)
Ilex namkadingensis V.S.Dang, Tagane & Soulad., a new species of Aquifoliaceae from Bolikhamxai, central Laos, is described and illustrated. The new species is morphologically similar to Ilex rubrinervia Tardieu but differs in having larger leaf blades, longer petioles, and larger and 6- or 7-seeded fruits. Photographs, descriptions, conservation status and vernacular name of the new species are provided.